Use of ultramolecular potencies of allergen to treat asthmatic people allergic to house dust mite: double blind randomised controlled clinical trial. Issue 7336 (2nd March 2002) - Lewith, G T; Watkins, A D; Hyland, M E; Shaw, S; Broomfield, J A; Dolan, G; Holgate, S T
Abstract: Objective: To evaluate the efficacy of homoeopathic immunotherapy on lung function and respiratory symptoms in asthmatic people allergic to house dust mite. Design: Double blind randomised controlled trial. Setting: 38 general practices in Hampshire and Dorset. Participants: 242 people with asthma and positive results to skin prick test for house dust mite; 202 completed clinic based assessments, and 186 completed diary based assessments. Intervention: After a four week baseline assessment, participants were randomised to receive oral homoeopathic immunotherapy or placebo and then assessed over 16 weeks with three clinic visits and diary assessments every other week. Outcome measure: Clinic based assessments: forced expiratory volume in one second (FEV1 ), quality of life, and mood. Diary based assessments: morning and evening peak expiratory flow, visual analogue scale of severity of asthma, quality of life, and daily mood. Results: There was no difference in most outcomes between placebo and homoeopathic immunotherapy. There was a different pattern of change over the trial for three of the diary assessments: morning peak expiratory flow (P=0.025), visual analogue scale (P=0.017), and mood (P=0.035). At week three there was significant deterioration for visual analogue scale (P=0.047) and mood (P=0.013) in the homoeopathic immunotherapy group compared with the placebo group. Any improvement in participants' asthma was independent of belief in complementary medicine. Conclusion: Homoeopathic immunotherapy is not effective in the treatment of patients with asthma. The different patterns of change between homoeopathic immunotherapy and placebo over the course of the study are unexplained.